Petrological and geochronological constraints on lower crust exhumation during Paleoproterozoic (Eburnean) orogeny, NW Ghana, West African Craton. (3rd April 2015) - Block, S.; Ganne, J.; Baratoux, L.; Zeh, A.; Parra‐Avila, L. A.; Jessell, M.; Ailleres, L.; Siebenaller, L.
Abstract New petrological and geochronological data are presented on high‐grade ortho‐ and paragneisses from northwestern Ghana, forming part of the Paleoproterozoic (2.25–2.00 Ga) West African Craton. The study area is located in the interference zone between N–S and NE–SW‐trending craton‐scale shear zones, formed during the Eburnean orogeny (2.15–2.00 Ga). High‐grade metamorphic domains are separated from low‐grade greenstone belts by high‐strain zones, including early thrusts, extensional detachments and late‐stage strike‐slip shear zones. Paragneisses sporadically preserve high‐pressure, low‐temperature (HP–LT) relicts, formed at the transition between the blueschist facies and the epidote–amphibolite sub‐facies (10.0–14.0 kbar, 520–600 °C), and represent a low ( 15 °C km−1) apparent geothermal gradient. Migmatites record metamorphic conditions at the amphibolite–granulite facies transition. They reveal a clockwise pressure–temperature–time (P–T–t) path characterized by melting at pressures over 10.0 kbar, followed by decompression and heating to peak temperatures of 750 °C at 5.0–8.0 kbar, which fit a 30 °C km−1 apparent geotherm. A regional amphibolite facies metamorphic overprint is recorded by rocks that followed a clockwise P–T–t path, characterized by peak metamorphic conditions of 7.0–10.0 kbar at 550–680 °C, which match a 20–25 °C km−1 apparent geotherm. These P–T conditions were reached after prograde burial and heating for some rock units, and after decompression and heating for others. The timing of anatexis and of the amphibolite facies metamorphic overprint is constrained by in‐situ U–Pb dating of monazite crystallization at 2138 ± 7 and 2130 ± 7 Ma respectively. The new data set challenges the interpretation that metamorphic breaks in the West African Craton are due to diachronous Birimian 'basins' overlying a gneissic basement. It suggests that the lower crust was exhumed along reverse, normal and transcurrent shear zones and juxtaposed against shallow crustal slices during the Eburnean orogeny. The craton in NW Ghana is made of distinct fragments with contrasting tectono‐metamorphic histories. The range of metamorphic conditions and the sharp lateral metamorphic gradients are inconsistent with 'hot orogeny' models proposed for many Precambrian provinces. These findings shed new light on the geodynamic setting of craton assembly and stabilization in the Paleoproterozoic. It is suggested that the metamorphic record of the West African Craton is characteristic of Paleoproterozoic plate tectonics and illustrates a transition between Archean and Phanerozoic orogens.